2000
DOI: 10.1258/0956462001915183
|View full text |Cite
|
Sign up to set email alerts
|

CMV colitis in early HIV infection

Abstract: Cytomegalovirus (CMV) colitis is a well recognized complication of advanced HIV disease and is only rarely diagnosed in patients with normal immune function. A case of CMV colitis occurring in early HIV infection is described. Although CMV infection is normally confined to patients with advanced HIV disease, it is possible that a number of contributing factors may have led to clinical disease in this patient. CMV colitis is an important diagnosis to consider in all patients who present with a diarrhoeal illnes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2003
2003
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 0 publications
0
7
0
Order By: Relevance
“…Intense symptoms occurred only 9 days after the diagnosis of primary HIV infection, and the patient had a normal CD4 cell count and did not initiate combination ART at that time. Smith et al [4] reported a case of CMV colitis during early HIV infection, with their patient only retrospectively receiving a diagnosis of HIV infection. This patient had not received combination ART, and HIV seroconversion was suspected to have occurred ∼4 months prior to diagnosis of CMV colitis.…”
mentioning
confidence: 99%
“…Intense symptoms occurred only 9 days after the diagnosis of primary HIV infection, and the patient had a normal CD4 cell count and did not initiate combination ART at that time. Smith et al [4] reported a case of CMV colitis during early HIV infection, with their patient only retrospectively receiving a diagnosis of HIV infection. This patient had not received combination ART, and HIV seroconversion was suspected to have occurred ∼4 months prior to diagnosis of CMV colitis.…”
mentioning
confidence: 99%
“…There are reports about CMV-colitis in early HIV-infection, in which a transient immune dysfunction is assumed despite relatively high CD4 counts, but these seem to take a more beneficial course (3,4). Here, the symptoms resolved only slowly.…”
Section: Discussionmentioning
confidence: 93%
“…Although CMV disease is frequently an opportunistic infection in the late course of AIDS, primary CMV disease occurring during the acute retroviral syndrome has rarely been documented. Zhao et al reported a case of CMV pneumonitis as an initial manifestation of HIV infection for the first time, and seven reports in the literature mentioned acute CMV disease in primary HIV infection [14][15][16][17][18][19][20]. Capetti et al, Smith et al, and Gupta reported cases of CMV colitis during early HIV infection, in which the patients had not received combination ART [15,16,19].…”
Section: Discussionmentioning
confidence: 99%
“…Zhao et al reported a case of CMV pneumonitis as an initial manifestation of HIV infection for the first time, and seven reports in the literature mentioned acute CMV disease in primary HIV infection [14][15][16][17][18][19][20]. Capetti et al, Smith et al, and Gupta reported cases of CMV colitis during early HIV infection, in which the patients had not received combination ART [15,16,19]. von Both et al [17] presented a case of reactivated intestinal CMV disease associated with immune reconstitution inflammatory syndrome that occurred during primary HIV infection.…”
Section: Discussionmentioning
confidence: 99%